Microbiome and metabolomics analyses of the effect of heat-sensitive moxibustion on allergic rhinitis in rats - Xiong, Jun; Li, Jianheng; Xu, Haiyan; Li, Yicheng; Lu, Lunbin; Yang, Shuang (Frontiers in Immunology, 2025)
BackgroundThe original concept of acupoint sensitization theory was put forward in Huangdi Neijing, which believed that acupoints, as the reflecting parts of the body surface, are personalized, changeable, and sensitive. Heat-sensitive moxibustion has a good therapeutic effect on allergic rhinitis, but the mechanism is still unclear. Notably, acupoint sensitization in allergic rhinitis (AR) rats was accompanied by a distal thermal effect, with an increase in tail temperature (TTI) after 40 min of moxibustion.ObjectiveThe objective was to utilize multi-omics techniques and correlation analysis to explore the unique mechanisms of heat-sensitive moxibustion in intervening in AR compared with traditional moxibustion from the perspectives of gut microbiota and metabolites.MethodsThirty-six Sprague–Dawley (SD) rats were randomly divided into two groups: the ovalbumin (OVA) group (n = 27) and the control group (Con) (n = 9). The rat model of AR induced by standardized OVA was established through intranasal infusion after intraperitoneal OVA injection. Through behavioral scoring, nasal symptoms were evaluated, including nasal scratching, runny nose, and sneezing, to ensure the success of the modeling. The OVA group was randomly divided into the moxibustion group (n = 17) and the AR group (n = 8). Then, through suspended moxibustion for 40 min, they were divided into TTI, namely, the heat-sensitive moxibustion group (HM) (n = 8) and the non-TTI group (OM) (n = 8), and one subject was excluded. The levels of serum IL-4 and IgE were quantified by enzyme-linked immunosorbent assay (ELISA), and the histological characteristics of nasal tissues were evaluated by hematoxylin and eosin (H&E) staining to determine the reliability of the AR rat model and the effectiveness of thermal sensitization. The V3 and V4 regions of the 16S ribosomal DNA (rDNA) gene were analyzed from rat feces using 16S rDNA sequencing technology. In addition, non-targeted metabolomics was used to identify the differential metabolites in rat urine. Finally, through the comparison and correlation analysis of different bacterial microbiota and metabolites, we aimed to clarify the unique material basis of heat-sensitive moxibustion in the context of AR.ResultsAfter the OVA modeling was completed, through behavioral score evaluation, we found that there were differences between the OVA group and the control group. After the intervention treatment, it was found that the levels of IgE and IL-4 in the AR group were significantly higher than those in the control group. Staining showed that moxibustion relieved nasal symptoms, and the thermal sensitization effect was satisfactory. We noticed that significant changes occurred in the flora under heat-sensitive moxibustion treatment. We investigated the mechanism of HM in treating AR using an integrated 16S rRNA sequencing technology and untargeted metabolomics. Our results showed that HM treatment ameliorated AR in rats. The high-throughput sequencing results indicate that HM significantly increased the relative abundance of species, such as Patescibacteria, Saccharimonadaceae, UCG-010, Butyrivibrio, Turicibacter, Lactobacillus murinus, and Adlercreutzia, while decreasing the relative abundance of Prevotellaceae. This shift in microbial composition is conducive to improving the gut microbiota of AR rats. Untargeted metabolomics results showed that HM treatment regulated the metabolites such as 1-methylhistidine, xi-3-hydroxy-5-phenylpentanoic acid O-beta-d-glucopyranoside, cladosporin, cuminaldehyde, daidzein, Pe(18:0/15:0), N-nervonoyl asparagine, edulitine, N-arachidonoyl glycine, 9alpha-(3-methyl-2E-pentenoyloxy)-4S-hydroxy-10(14)-oplopen-3-one, quisqualic acid, ethyl glucuronide, zileuton O-glucuronide, trichloroethanol glucuronide, Asp Leu Ser Glu, quinolinic acid, and norvaline. We finally identified six crossing pathways by pin-to-pair comparison of three groups: glutamatergic synapse, dopaminergic synapse, Kaposi sarcoma-associated herpesvirus infection, cocaine addiction, melanin production, alcoholism, and histidine metabolism. Subsequently, we focused on studying the histidine metabolism. To clarify the changes in the activity of this pathway, we measured the histamine content using an enzyme-linked immunosorbent assay. Compared with the OM group, we found that HM had a trend toward superior efficacy in reducing tissue histamine compared to OM. The histamine content in the HM group was significantly lower than that in the OM group. This finding suggests that HM is more effective in reducing histamine, and its effect may be related to a more efficient regulation of the histidine metabolic pathway.ConclusionsThis study demonstrates that heat-sensitive moxibustion alleviates allergic rhinitis through a multi-targeted mechanism involving both the modulation of specific gut microbiota (notably L. murinus, Patescibacteria, Butyrivibrio, and Turicibacter)—which is closely associated with alterations in key metabolites (cuminaldehyde and 1-methylhistidine)—and the regulation of histidine metabolism. To our knowledge, this represents the first investigation to establish comprehensive correlations between gut microbiota and urinary metabolomics profiles in an AR model. Our findings confirm the therapeutic role of heat-sensitive moxibustion in AR recovery and provide mechanistic insights supporting its clinical application, thereby proposing a novel strategic approach for AR treatment.